2020
DOI: 10.3389/fimmu.2020.02138
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Metabolites Were Altered, Identified as Biomarkers and Correlated With Disease Activity in Patients With Systemic Lupus Erythematosus in a GC-MS-Based Metabolomics Study

Abstract: Gut metabolites are products of the crosstalk between microbes and their host and play an important role in the occurrence, development, diagnosis, and treatment of autoimmune diseases. This work profiled the fecal metabolome of patients with systemic lupus erythematosus (SLE) using gas chromatography-mass spectrometry (GC-MS) and analyzed the potential roles of metabolites in the diagnosis and development of SLE. Fecal sample from 29 SLE patients without any other diseases and 30 healthy controls (HCs) were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 36 publications
1
28
1
Order By: Relevance
“…Additionally, several studies used various analytical methods to demonstrate that cyclophosphamide can reduce the fecal levels of short-chain fatty acids beneficial to health (e.g., acetic acid, propionic acid, butyric acid, and valeric acid), and these effects are reversed after treatment with various agents, e.g., exopolysaccharides ( 26 , 30 ). Detection of these compounds by different analytical methods may produce variable results ( 39 ); hence, these results in combination with the data of the present study more comprehensively describe the effects of cyclophosphamide and of the treatments by microbes or other substances on gut metabolism.…”
Section: Discussionmentioning
confidence: 60%
“…Additionally, several studies used various analytical methods to demonstrate that cyclophosphamide can reduce the fecal levels of short-chain fatty acids beneficial to health (e.g., acetic acid, propionic acid, butyric acid, and valeric acid), and these effects are reversed after treatment with various agents, e.g., exopolysaccharides ( 26 , 30 ). Detection of these compounds by different analytical methods may produce variable results ( 39 ); hence, these results in combination with the data of the present study more comprehensively describe the effects of cyclophosphamide and of the treatments by microbes or other substances on gut metabolism.…”
Section: Discussionmentioning
confidence: 60%
“…Previous metabolomic studies have shown an association between a disturbance of amino acid metabolism and autoimmune disease and a certain amino acid profile might have a diagnostic potential ( Fernández-Ochoa et al, 2019 ; Thoman and McKarns, 2020 ; Yan et al, 2020 ). Similarly, we found that amino acids were differentially expressed in urine from VKH patients and they were the most abundant differential metabolites in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The metabolome is now considered to play a key role in SLE due to developments in mass-spectrometry-based metabolic flux analysis. The fecal metabolomes of 29 SLE patients and 30 healthy controls were analyzed by gas chromatography-mass spectrometry [117]. The results suggest that L-valine, pyrimidine, erucamide, and L-leucine are excellent potential diagnostic biomarkers for SLE, and alterations of fecal metabolites are closely correlated with SLE [117].…”
Section: Metabolome In Slementioning
confidence: 99%
“…The fecal metabolomes of 29 SLE patients and 30 healthy controls were analyzed by gas chromatography-mass spectrometry [117]. The results suggest that L-valine, pyrimidine, erucamide, and L-leucine are excellent potential diagnostic biomarkers for SLE, and alterations of fecal metabolites are closely correlated with SLE [117]. Proteomic profiling of kidney tissues from SLE revealed that coronin-1A is a biomarker of LN, and the level of it in serum can distinguish LN patients from SLE patients without nephritis with 100% sensitivity and 100% specificity [118].…”
Section: Metabolome In Slementioning
confidence: 99%